Comparison of the effects of in-person and internet-delivered mindfulness-based stress reduction on the burden of psychosomatic symptoms in nurses - Al-Badiri, Muhmmad Qabil Jamil; Ghadirian, Fataneh; Zahednezhad, Hosein; Boozari, Mahsa; Hayati, Mahsa-Sadat (Frontiers in Psychology, 2024)
Introduction There is some evidence comparing the efficacy of telehealth to in-person mental health care, but there is limited research specifically comparing these modalities in nurses. The study aimed to compare the effects of Mindfulness-based Stress Reduction (MBSR) and Internet-delivered Mindfulness-based Stress Reduction (iMBSR) on burden of psychosomatic symptoms of nurses working at Al-Alhamzeh general hospital, Aldiwaniyeh, Iraq. Methods The study was a semi-experiment study with a pre-posttest design on 72 registered nurses. Subjects were randomly allocated in group A, in-person MBSR and group B, internet-delivered MBSR. Intervention in two groups was held at 8 weekly sessions. The data collection instrument included sociodemographic, Patient Questionnaire Health-15 (PHQ-15), and General Health Questionnaire-12 (GHQ-12). Data were analyzed with SPSS version 24 by descriptive and non-parametric inferential tests. Results The study found that 50% of the nurses in both groups reported mild somatic symptoms, and 40% reported moderate symptoms, with the majority showing no signs of mental distress. A more significant reduction in GHQ scores compared to PHQ scores was observed from pre-to post-intervention. Notably, the online MBSR group showed a significant decrease in GHQ scores, both between groups (p = 0.04) and within the online MBSR group itself (p = 0.02), highlighting the greater impact of the intervention in this group. Conclusion The study highlights the positive effects of both in-person and online MBSR interventions on reducing depressive symptoms and improving mental health outcomes among nurses. Online MBSR, in particular, shows promise in addressing medically unexplained symptoms and enhancing mental well-being.